Fluoxetine impairs GABAergic signaling in hippocampal slices from neonatal rats - Cherubini, Enrico; Caiati, Maddalena D. (Frontiers in Cellular Neuroscience, 2013)
Fluoxetine (Prozac), an antidepressant known to selectively inhibit serotonin reuptake, is widely used to treat mood disorders in women suffering from depression during pregnancy and postpartum period. Several lines of evidence suggest that this drug, which crosses the human placenta and is secreted into milk during lactation, exerts its action not only by interfering with serotoninergic but also with GABAergic transmission. GABA is known to play a crucial role in the construction of neuronal circuits early in postnatal development. The immature hippocampus is characterized by an early type of network activity, the so-called Giant Depolarizing Potentials (GDPs), generated by the synergistic action of glutamate and GABA, both depolarizing and excitatory. Here we tested the hypothesis that fluoxetine may interfere with GABAergic signaling during the first postnatal week, thus producing harmful effects on brain development. At micromolar concentrations fluoxetine severely depressed GDPs frequency (IC50 22 M) in a reversible manner and independently of its action on serotonin reuptake. This effect was dependent on a reduced GABAergic (but not glutamatergic) drive to principal cells most probably from parvalbumin-positive fast spiking neurons. Cholecystokinin-positive GABAergic interneurons were not involved since the effects of the drug persisted when cannabinoid receptors were occluded with WIN55,212-2, a CB1/CB2 receptor agonist. Fluoxetine effects on GABAergic transmission were associated with a reduced firing rate of both principal cells and interneurons further suggesting that changes in network excitability account for GDPs disruption. This may have critical consequences on the functional organization and stabilization of neuronal circuits early in postnatal development.